2013
DOI: 10.1111/srt.12088
|View full text |Cite
|
Sign up to set email alerts
|

Striae distensae are characterized by distinct microstructural features as measured by non‐invasive methods in vivo

Abstract: The skin structure of SD is qualitatively and quantitatively different compared to healthy skin. Altered skin relief reflects structural modifications in the dermis. Flattening of the dermal-epidermal junction maybe functionally related to the observed collagen fiber alignment. Observations by non-invasive methods were in line with the histological findings and therefore relevant in studies assessing the efficacy of SD treatment options.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
27
1
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 12 publications
3
27
1
4
Order By: Relevance
“…As SD develop, the physical stretching of the inner structures causes the skin surface to be elongated directionally, forming bigger and longer blob with anisotropic properties. Our findings are in accordance with those of a previous study, which indicated a more anisotropic surface of SD‐involved skin microrelief analyzed from replica images . Another study reported that the SD‐involved skin has a preferred propagation direction, which was confirmed in our study as well.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…As SD develop, the physical stretching of the inner structures causes the skin surface to be elongated directionally, forming bigger and longer blob with anisotropic properties. Our findings are in accordance with those of a previous study, which indicated a more anisotropic surface of SD‐involved skin microrelief analyzed from replica images . Another study reported that the SD‐involved skin has a preferred propagation direction, which was confirmed in our study as well.…”
Section: Discussionsupporting
confidence: 93%
“…Measurements of SD are essential to study the etiological mechanism and to evaluate the clinical efficacy of various treatments. Heretofore, there have been many studies about the clinical evaluation of SD, including visual assessments, objective measurement of biophysical properties, and histologic observations of SD . However, no standard non‐invasive objective method has been suggested yet.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…demonstrated that SD skin had significantly higher values in the surface roughness than normal skin. Continuous structure modifications of skin relief were associated with a decrease in the elastic fiber network of the papillary dermis . We identified the consistency results that the roughness of SD‐involved skin showed higher values in Ra, Rz, and Rt parameters as shown in Figure E,F and Figure .…”
Section: Discussionmentioning
confidence: 93%
“…Moreover, other studies described that the SD‐involved skin has significantly less elasticity and exhibited less deformability than normal skin. Bertin et al., using three‐dimensional measurement, reported that the surface of SD skin is rougher and more anisotropic than that of normal skin . Ultrasound technique has been used as an efficient method to visualize the changes in the characteristics of the dermis .…”
Section: Introductionmentioning
confidence: 99%